Inclusion: humanization as fundament of ducative quality (Ágora de Heterodoxias, 2017)
This essay aims to contribute in the discussion and reflection about humanization as a principle to incorporate inclusive and quality spaces in education in Costa Rica. For this reason, it compiles a series of reflections exposed by several authors on the implications of the concept of inclusion in areas such as education, sociocultural sphere as well as the socioeconomic and political ones. It also addresses to aspects that reinforce exclusion of people with different conditions.  Hence the author highlights the abilities and rights of all people to access and participate with equality in regular and quality educational services, highlighting the vision of integration by inclusion.
Keywords: access to education; quality of education; humanism; exclusion; inclusive spaces